2015
DOI: 10.1371/journal.pone.0132509
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis of Poplar Seed Vigor

Abstract: Seed vigor is a complex property that determines the seed’s potential for rapid uniform emergence and subsequent growth. However, the mechanism for change in seed vigor is poorly understood. The seeds of poplar (Populus × Canadensis Moench), which are short-lived, were stored at 30°C and 75±5% relative humidity for different periods of time (0–90 days) to obtain different vigor seeds (from 95 to 0% germination). With decreasing seed vigor, the temperature range of seed germination became narrower; the respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 75 publications
(81 reference statements)
7
31
0
1
Order By: Relevance
“…However, germination data cannot be extrapolated to the field; this is mainly because germination tests assume ideal conditions, which is contrary to the sub-optimal conditions actually present in the field [5]. Therefore, biological quality should also be measured by another concept, namely vigor, which can be more assertive in the measurement of germination rate, uniformity, and growth [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, germination data cannot be extrapolated to the field; this is mainly because germination tests assume ideal conditions, which is contrary to the sub-optimal conditions actually present in the field [5]. Therefore, biological quality should also be measured by another concept, namely vigor, which can be more assertive in the measurement of germination rate, uniformity, and growth [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, another report showed that the application of PGPR recovered the expression level of this protein under stress conditions (Li et al, 2013b). The CPN20 (spot 23), which was among the most-represented proteins that emphasize the impact of stress on post-translation modification/ modification machinery (Zhang et al, 2015) showed similar results when inoculated with FOC.…”
Section: Discussionmentioning
confidence: 84%
“…So far, many researchers have investigated seed vigor at protein level [10][11][12][13][14][15][16][17][18][19][20]. Recently, several proteomic studies have focused on the effects of HTH stress on the vigor formation of developing soybean seed.…”
Section: Introductionmentioning
confidence: 99%